Detection of hypoxia in the pulmonary tissues of Xenopus laevis over repeated dives. (24th January 2023) - Fujiyama, Shingo; Okui, Takehito; Kato, Takashi
Abstract: The oxygen environment in African clawed frogs ( Xenopus laevis ) continuously changes during their development, which involves a rapid increase in the body size, metamorphosis, and transition to adulthood. Nevertheless, there are limited reports on experimental models that are available for studying fluctuations in the oxygen environment in X. laevis . Thus, this study aimed to develop an experimental model on intermittent hypoxia in X. laevis and evaluate hypoxia and oxidative stress in the same. X. laevis were submerged in water with a dissolved oxygen concentration of 2 mg/L for 30 min; they were then removed from the water and allowed to freely absorb oxygen for 5 min. Immunostaining of pimonidazole‐containing frozen tissue sections of the lung and liver using anti‐pimonidazole antibodies as the hypoxia probes revealed that more than 95% of the submerged X. laevis cells were pimonidazole positive, providing direct evidence of tissue hypoxia. When the amount of oxidative stress in the lungs and liver was evaluated in terms of the amount of lipid peroxides, the diving group showed a 2.08‐fold and 3.20‐fold increase over the normal group, respectively. Following hypoxia exposure, the dry‐to‐wet weight ratios of the lung tissues was 1.27 times higher ( p  < .05), while the liver tissues was 1.06 times higher (although not significant). Thus, the degree of damage depended on the tissues affected. In the future, we believe that this model will be a promising option for analyzing the physiological responses of X. laevis to hypoxia and oxidative stress. Abstract : This study established a model of intermittent hypoxia in African clawed frogs.